Amy Goldman: The Heirloom Tomato. From Garden to Table - Jaine, Tom (Petits Propos Culinaires, 2012)
Amy Goldman: The Heirloom Tomato. From Garden to Table: Bloomsbury, 2008, 260 pp., hardback, £25.00.